A Preliminary Conceptual Design Approach Of Food Waste Composter Design - Mat Tokit, Ernie; Ng, Angie; Mohd Saat, Fatimah Al Zahrah; Abd Rahman, Norasra; Shikh Anuar, Fadhilah; M. Mitan, Nona Merry (Novel Carbon Resource Sciences, 2021)
This paper reports the conceptual design of a household kitchen food waste composter. Several conceptual approaches, such as Quality Function Deployment (QFD), Concept Generation, and Concept of Evaluation using PUGH Method are implemented. The component selection is applied using House of Quality method, and the final design is presented and selected using PUGH Method. Design 1 is selected as the best composter design. The material selection and the cost of the components are also presented. The conceptual design approach highlights its benefit as the preliminary method in designing the food waste composter.